GGE Biplot Analysis for Yield Stability in Multi-environment Trials of Promising Hybrid Rice (Oryza sativa L.) (Bangladesh Rice Journal, 2015)
The genotype and genotype by environment biplot model is an excellent tool for visual multi-environment trials data analysis. In this study we investigated grain yield of six rice genotypes (three tested, one released hybrids and two inbred check varieties) in five environments. The combined analysis of variance for grain yield data indicated that the differences among all sources of variation were highly significant (P0 classified the high yielding genotypes while PC1 scores0) while another vertex genotype BRRI dhan28 (G5) produced low yield (PC1 score